2008
DOI: 10.1089/ars.2007.1830
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and Repair: From Molecular Mechanisms to Health Implications

Abstract: DNA is subjected to several modifications, resulting from endogenous and exogenous sources. The cell has developed a network of complementary DNA-repair mechanisms, and in the human genome, >130 genes have been found to be involved. Knowledge about the basic mechanisms for DNA repair has revealed an unexpected complexity, with overlapping specificity within the same pathway, as well as extensive functional interactions between proteins involved in repair pathways. Unrepaired or improperly repaired DNA lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
124
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 256 publications
0
124
0
4
Order By: Relevance
“…Left untreated, it will spread throughout the body and becomes fatal. Chemotherapy (the use of cytotoxic agents to slow the progression of this uncontrolled cell division) is the major treatment when cancer is well established within the patient [2]. Resistance to anticancer drugs is a major problem in chemotherapy with 30% -80% of cancer patients developing resistance to chemotherapeutical drugs [3].…”
Section: Cancermentioning
confidence: 99%
“…Left untreated, it will spread throughout the body and becomes fatal. Chemotherapy (the use of cytotoxic agents to slow the progression of this uncontrolled cell division) is the major treatment when cancer is well established within the patient [2]. Resistance to anticancer drugs is a major problem in chemotherapy with 30% -80% of cancer patients developing resistance to chemotherapeutical drugs [3].…”
Section: Cancermentioning
confidence: 99%
“…Another conceptual problem has been the known lesion cross-specificity between repair pathways, which affords multiple enzymatic avenues for repair of any particular class of lesion, and builds a certain level of pathway redundancy that would seem difficult to target with a single inhibitory agent. 12 Despite earlier difficulties, recent developments in our understanding of the molecular biology of tumors have, nevertheless, exposed the details of human DNA repair and revealed molecular differentials between tumor and normal cells. 13,14 In addition, there are now better research tools for probing the mechanistic aspects of DNA repair, which have also suggested new DNA repair targets.…”
Section: Issuesmentioning
confidence: 99%
“…Such damage, if left unrepaired, can cause mutations, which can lead to disease. To protect against genome instability and its dangerous consequences organisms have developed several DNA repair pathways [123].…”
Section: Dna Damagementioning
confidence: 99%